Selected Lectures of the Round Table on “Antibiotic Resistance and Endocrine Disruptors”; Cagliari (Italy); October 25, 2025 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2025)
Selected Lectures of the Round Table on “Antibiotic Resistance and Endocrine Disruptors”; Cagliari (Italy); October 25th, 2025 The Round Table on “Antibiotic Resistance and Endocrine Disruptors” is a Satellite Meeting of the 21st International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 22nd-25th, 2025. LECT 1. ANTIMICROBIAL RESISTANCE AND ENDOCRINE DISRUPTING CHEMICALS (EDCs) • M.E. Street, A.M. Shulhai, P. Palanza (Parma, Italy) LECT 2. NEW ANTIMICROBIALS FOR EMERGING AND RE-EMERGING PATHOGENS • A. Scano (Cagliari, Italy) LECT 3. ANTIBIOTIC RESISTANCE IN INTENSIVE CARE • G. Finco, L. Congiu, M. Musu, S. Sardo (Cagliari, Italy) LECT 4. ANTIBIOTIC RESISTANCE IN NEONATAL INTENSIVE CARE • F. Zanco, M. Melis, V. Fanos (Cagliari, Italy) LECT 5. UNDERSTAFFING AND OVERCROWDING IN NEONATAL INTENSIVE CARE UNITS • D. Pisano (Cagliari, Italy) LECT 6. ANTIBIOTIC RESISTANCE IN PEDIATRIC SURGICAL CARE: A NARRATIVE REVIEW INVESTIGATING AN EMERGING INVISIBLE SURGICAL CHALLENGE • B. Sanna, L. Mascia (Cagliari, Italy) LECT 7. ANTIBIOTIC RESISTANCE IN ANIMAL FARMING: THE ADVANTAGES OF ORGANIC FARMING • P. Armento (Sesto Fiorentino, Italy)